Review of the traineeship at the University of Prešov - Stepanenko, Anastasiia (Ukrainian Cultural Studies, 2024)
The University of Prešov is one of the leading higher education institutions in Slovakia, located in the city of Prešov. Founded in 1997, the university quickly established itself as an important educational and scientific center of the region. It offers a wide range of academic programs at bachelor's, master's and doctoral levels covering various fields of knowledge, including humanities, social sciences, natural sciences, theology, medicine and others. Training programs are aimed at developing critical thinking, practical skills and academic excellence.